Asimetri Informasi, Leverage, dan Ukuran Perusahaan pada Manajemen Laba - Mahawyahrti, Tiya; Budiasih, Gusti Nyoman (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 11 No 2 (2016), 2017)
This study aims at finding the empirical evidence of the effect of asymmetry information, leverage, and firm size on earning management. This research uses agency theory and positive accounting theory to explain the effect of asymmetry information, leverage, and firm size on earning management. This study was conducted on companies listed in Indonesia Stock Exchange during the period of 2009-2013. The samples were selected by purposive sampling method. The number of selected samples were 39 companies. Multiple linear regression analysis was used to analyze the data. Based on the data analysis, the study proves that the asymmetry information has positive effects on earning management, leverage has positive effects on earning management and firm size has negative effects on earning management.
Keywords: Information Asymmetry, Leverage, Firm Size and Earnings Management